2020
DOI: 10.3390/molecules25030510
|View full text |Cite
|
Sign up to set email alerts
|

Bioactives from Agri-Food Wastes: Present Insights and Future Challenges

Abstract: Sustainable utilization of agri-food wastes and by-products for producing value-added products (for cosmetic, pharmaceutical or food industrial applications) provides an opportunity for earning additional income for the dependent industrial sector. Besides, effective valorisation of wastes/by-products can efficiently help in reducing environmental stress by decreasing unwarranted pollution. The major focus of this review is to provide comprehensive information on valorisation of agri-food wastes and by-product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
187
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 328 publications
(195 citation statements)
references
References 174 publications
1
187
0
7
Order By: Relevance
“…However, studies related to the extractions of such functional ingredients concentrate mainly on the extraction technologies, and there are relatively few studies on the applications of these extracts in food products. Adapted and modified from [72,73].…”
Section: Major Functional Ingredients and Bioactives That Can Be Extrmentioning
confidence: 99%
“…However, studies related to the extractions of such functional ingredients concentrate mainly on the extraction technologies, and there are relatively few studies on the applications of these extracts in food products. Adapted and modified from [72,73].…”
Section: Major Functional Ingredients and Bioactives That Can Be Extrmentioning
confidence: 99%
“…Juice processing by-products are usually buried directly in the soil, which causes serious environmental pollution [9]. However, these by-products still contain bioactive compounds such as tannins, flavonoids, flavanols, vitamins, essential minerals, fatty acids, volatiles, and pigments, which can be utilized as natural bioactive compounds [10]. The scientific community has suggested the use of these natural compounds instead of synthetic compounds due to their synergy, potency, and minimal side effects [11].…”
Section: Introductionmentioning
confidence: 99%
“…Most fruit wastes have been utilized as a source of livestock feeds or as organic fertilizers. Since non-edible parts of fruit such as peel, skin parts, and seed often contain higher amounts of bioactive compounds than the edible parts, it has attracted attention to obtain the bioactive compounds in the wastes [1][2][3][4]. One of the most common target compounds from fruit wastes is polyphenols.…”
Section: Discussionmentioning
confidence: 99%
“…Fruits and their industries generate large quantities of waste and by-products, and the management of waste and by-products is one of the major environmental issues [1][2][3][4]. On the other hand, recent research has showed that it is rich in potentially valuable components such as polyphenol, pigments, and vitamins in the waste and by-products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation